Two new species and a new record of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India with an updated key to species of subgenus Bactrocera - Abhishek, Venkateshaiah; David, Karamankodu Jacob; Pradeep, Shivanand (Zootaxa, 2024)
Two new species of genus Bactrocera Macquart, namely Bactrocera (Bactrocera) ettinanhuja Abhishek and David, sp. nov. and Bactrocera (Bactrocera) kyrdemkulai Abhishek & David, sp. nov., are described from Western Ghats and Northeast India, respectively. Bactrocera (Bactrocera) wuzhishana Lin & Yang, is recorded for the first time from India. An updated key to Indian fruit flies of subgenus Bactrocera Macquart is also provided.